Respuesta :

Answer:

Step-by-step explanation:

4x - 9 = 9x - 34

-5x - 9 = -34

-5x = -25

x = 5

4(5) - 9 + 9(5) - 34

20 - 9 + 45 - 34

11 + 11 = 22

Answer:

CT = 22

Step-by-step explanation:

given:

         4x - 9                                9x - 34

|-------------------------------|----------------------------------|

C                                   J                                     T

find:  CT

CJ + JT = CT -----------eq. 1

CJ = JT -------------------eq.2

plugin values using eq.2

4x - 9 = 9x - 34

combine like terms:

4x - 9x = 9 - 34

-5x = -25

x = -25 / -5

x = 5

solve for CT using eq.1

CJ + JT = CT

4x - 9 + 9x - 34 = CT

substitute x to 5

4(5) - 9 + 9(5) - 34 = CT

20 - 9 + 45 - 34 = CT

22 = CT

therefore,

CT = 22